Curbing the Trend of Violence in the Nigerian Society: The Violence against Persons (Prohibition) Act, 2015 - Ibraheem, Tajudeen Ojo (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
Violence exists throughout the world without respect for national, ethnic or cultural boundaries. Despite the number of Nigerians who experience violence, until recently there was no comprehensive Federal legislation in place to prevent this violence, protect survivors or punish perpetrators. The Violence against Persons (Prohibition) Act 2015 was thus welcomed with joy by the populace. This paper briefly examines the background history of the Act, its major provisions and what positive effect, if any, the Act has had on the perpetration and perpetrators of violence in the country. The writer also considers the factors militating against a successful implementation of the provisions of the Act. Some suggestions are made at the end of the paper. The writer concludes that among other factors, a change in people’s attitudes towards violence is paramount to a successful implementation of the Act. Keywords: Act, Nigeria, persons, prohibition, violence